A politica fiscal no Brasil: limites e contradições: o caso do Estado do Espírito Santo - Vieira, Clóvis Abreu (1986)
This research intends to contribute to the analysis of the brazi1ian rea1ity through Espirito Santols case, comprehending the period Df 1946 to 1980, trying to demonstrate the financial dependency Df the state governments ref1ected on the 10ss of their own income and the.necessary autonomy for'its use. In a retrospective v i e I': i t has been observed an excessi ve tendency to centra1ization shown by the brazilian federa1ism main1y after the 1967 tax reform wich estab1ished·a strict control of the Union on the tax incomes and action of the states, reducing its autonomy on tax legislation. FinanciaI and political centralization caused the loss of the previously acquired privileges bj' the state governments as well as the limitation of the autonomy in terms of fiscal politics. There was an attempt.to compensate an outstanding reduci:.ion of the state tax incomes by establishing the transfers mechanism whlch despi te their redistributive functions imposes a series Df requirements' and determinations for its application. From this assertion on the fiscal politic starts to be analised in Espirito Santo State observing the state administration during this período We come to a conclusion that the constant financiaI crisis that occurred limi ted the creation of a state fiscal politics. With this, we know the states became mere adminis'crati ve agents just reproducing the major decisions ma de by the federal government. General speaking, the creias an attempt to prove the financial. deper:d8flcy analysis of the basis and the resources Df the allocation. It was observed that the economical basis did not permit the enlargement of the income taxes demonstrating a, high dependency of intergovernmental transfers and waiting for the enlargement of indebtment to serve the investment decisions. AlI this reflected on the expansion limitation of the public expenses. A high credit dependency did not permit the search af investments requested by the state development politics. Thedimension of the phenomenon was evaluated by the process of the resources allocation through the neoclassic and Marxist vision. lt is worth outstanding that the neoclassic vision revealed a conduction of the expenses to attend the public welfares, the investments, the social welfares and the ones relatedto the health and . education. But it was the analisys of the Maixist vision that made it possible to reveal the concentrati6n of the resources for the arran~1ement of the joint stock in damage of the ones related to the joint expenses of the production. P,nother important consequence of the financiaI dependency was the aggravation of state government's fiscal crisis. For this, there was the contribution of the pressures in favor af higher expenses which made easier the process of stock accumulation and in Espirito Santo's case also the ones manifested with the implantation of great projects. This monography intends to contribute to the coming deeper studies to éxplain the state government's financiaI dependency.